SMART PAWON: SMART PANTI ASUHAN WEB ON NETWORK SEBAGAI TEKNOLOGI TEPAT GUNA UNTUK PENGEMBANGAN PANTI ASUHAN DI KOTA MALANG - E., Elwin; S., Sutrisno; Prasetiyo, Azis Rizal (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Orphanages as institutions which accommodate, nurture, and educate orphans and underprivileged, majority are unable to survive long due to lack of public support. The lack of such assistance due to lack of publication of the existence of an orphanage to the general public and donors. To solve this problem, we did community service to orphanages in order to publicize its existence to the general public and donors with the title: Smart Pawon: âSmart Orphanage Web On Network as the Applied Technology for Developing Orphanage in Malang